Candidate Phyla Radiation (CPR) bacteria from hyperalkaline ecosystems provide novel insight into their symbiotic lifestyle and ecological implications - Yu He; Shiyan Zhuo; Meng Li; Jie Pan; Yongguang Jiang; Yidan Hu; Robert A. Sanford; Qin Lin; Weimin Sun; Na Wei; Shuming Peng; Zhou Jiang; et al. (Microbiome)
Abstract Background Candidate Phyla Radiation (CPR) represents a unique superphylum characterized by ultra-small cell size and symbiotic lifestyle. Although CPR bacteria have been identified in varied environments, their broader distribution, associations with hosts, and ecological roles remain largely unexplored. To address these knowledge gaps, a serpentinite-like environment was selected as a simplified model system to investigate the CPR communities in hyperalkaline environments and their association with hosts in extreme conditions. Additionally, the enzymatic activity, global distribution, and evolution of the CPR-derived genes encoding essential metabolites (e.g., folate or vitamin B9) were analyzed and assessed. Results In the highly alkaline serpentinite-like ecosystem (pH = 10.9–12.4), metagenomic analyses of the water and sediment samples revealed that CPR bacteria constituted 1.93–34.8% of the microbial communities. Metabolic reconstruction of 12 high-quality CPR metagenome-assembled genomes (MAGs) affiliated to the novel taxa from orders UBA6257, UBA9973, and Paceibacterales suggests that these bacteria lack the complete biosynthetic pathways for amino acids, lipids, and nucleotides. Notably, the CPR bacteria commonly harbored the genes associated with essential folate cofactor biosynthesis and metabolism, including dihydrofolate reductase (folA), serine hydroxymethyltransferase (glyA), and methylenetetrahydrofolate reductase (folD). Additionally, two presumed auxotrophic hosts, incapable of forming tetrahydrofolate (THF) due to the absence of folA, were identified as potential hosts for some CPR bacteria harboring folA genes. The functionality of these CPR-derived folA genes was experimentally verified by heterologous expression in the folA-deletion mutant Escherichia coli MG1655 ΔfolA. Further assessment of the available CPR genomes (n = 4,581) revealed that the genes encoding the proteins for the synthesis of bioactive folate derivatives (e.g., folA, glyA, and/or folD genes) were present in 90.8% of the genomes examined. It suggests potential widespread metabolic complementarity in folate biosynthesis between CPR and their hosts. Conclusions This finding deepens our understanding of the mechanisms of CPR-host symbiosis, providing novel insight into essential cofactor-dependent mutualistic CPR-host interactions. Our observations suggest that CPR bacteria may contribute to auxotrophic organisms and indirectly influence biogeochemical processes. Video Abstract